DAMPAK BANJIR WAY KEMILING DAN WAY PEMANGGILAN TERHADAP SOSIAL DAN EKONOMI MASYARAKAT - Margaretta Welly (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
Flooding is a natural occurrence that needs to be learned/character of its characteristics so as notto harm the community that exists around the River as well as the social and economic impact, es-pecially in communities around the River Way Kemiling and the Way Pemanggilan. The researchaimed to find out how large the impact of floods in terms of technical, as well as the social andeconomic society along the Way Kemiling and Way Pemanggilan who never had flooded. Re-search conducted since July to September 2012, with methods of field survey and fill out the ques-tionnaire directly to residents affected by flooding. Then conducted the calculation of flood dis-charge (Q) one-year anniversary of when the plans and capacity of the river channel. From theresults of the calculations predicted losses due to floods residents were more or less on averagefor each home is 5,82 million rupiah (this number is based on the origin's home around the site offlooding), this does not include the House's other residents. Debit calculation results shows thatexisting channels that exist have 12,52 capacity m 3/second, while the estimated discharge wouldhappen (annual discharge) reached 19,06 m3/second. So the existing channels will not be able tohold the excess water, let alone five annual floods.